2013
DOI: 10.2174/1573403x11309010003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Cardiovascular Disease in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic and multisystemic autoimmune disorder which predominantly affecting women. The most common cause of death in SLE patients affected by disease for more than 5 years is cardiovascular disease (CVD). Epidemiological observations suggest that, together with classical conventional risk factors, other mechanisms (non-conventional/disease-specific factors) promote accelerated atherosclerosis in inflammatory diseases like SLE. Traditional CVD risk factors included age, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The existence of hypertension and use of anti-hypertensive drugs might counteract the each effect. Corticosteroid is considered as a possible risk factor for cardiovascular disease in patients with systemic lupus erythematosus [20]. Korkmaz et al also implied that the prevalence of steroid therapy is higher among patients with systemic lupus erythematosus accompanied with, than without coronary atherosclerosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of hypertension and use of anti-hypertensive drugs might counteract the each effect. Corticosteroid is considered as a possible risk factor for cardiovascular disease in patients with systemic lupus erythematosus [20]. Korkmaz et al also implied that the prevalence of steroid therapy is higher among patients with systemic lupus erythematosus accompanied with, than without coronary atherosclerosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional CV risk factors such as diabetes mellitus (DM), hypertension (HT) and dyslipidaemia were reported to be increased in patients with LN as compared with patients with SLE without nephritis. [14][15][16][17] Other contributing factors for atherosclerotic CVD in patients with LN include presence of renal impairment and proteinuria. 17 18 Indeed, renal insufficiency and proteinuria are both well-recognised risk factors for atherosclerotic CVD, and CVD in fact is the leading cause of mortality in patients with renal failure.…”
Section: Lupus Science and Medicinementioning
confidence: 99%
“…pSS predominately affects females (9 : 1), with a frequency in the overall population from 0.1 to 0.6%. Studies evaluating patients with rheumatoid arthritis (RA) [2] and systemic lupus erythematosus (SLE) [103] have shown that inflammation plays a role in the progression of hypertension, diabetes mellitus, and MetS [104]. …”
Section: Id3 and Disease Outcomesmentioning
confidence: 99%